The pertinence of microwave irradiated coconut shell bio-sorbent for wastewater decolourization: structural morphology and adsorption optimization using the response surface method (RSM) - Mohammed, Abdulsalam; Che Man, Hasfalina; Idris, Aida Isma; Zainal Abidin, Zurina; Md Yunos, Khairul Faezah (MDPI, 2018)
Palm oil mill effluent contains carcinogenic coloured compounds that are difficult to separate due to their aromatic structure. Though colour treatment using adsorption processes at lower pH (<4) have been reported effectual, due to its acidity the remediated effluent poses an environmental hazard as a result. Thus, the current study focused on achieving decolourization at neutral pH by enhancing the morphology of the coconut shell activated carbon (CSAC) using N₂ as activating-agent with microwave irradiation heating. The microwave pretreated and non-pretreated CSAC were characterized using scanned electron microscopy (SEM), energy dispersive X-ray (EDX) and Brunauer-Emmett-Teller (BET) analysis. A significant modification in the porous structure with a 66.62% increase in the specific surface area was achieved after the pretreatment. The adsorption experimental matrix was developed using the central composite design to investigate the colour adsorption performance under varied pH (6⁻7), dosage (2⁻6 g) and contact time (10⁻100 min). At optimum conditions of neutral pH (7), 3.208 g dosage and contact time of 35 min, the percentage of colour removal was 96.29% with negligible differences compared with the predicted value, 95.855%. The adsorption equilibrium capacity of 1430.1 ADMI × mL/g was attained at the initial colour concentration of 2025 ADMI at 27 °C. The experimental data fitted better with the Freundlich isotherm model with R² 0.9851.